Indigenous peoples and local communities report ongoing and widespread climate change impacts on local social-ecological systems - Reyes-García, V.; García-del-Amo, D.; Álvarez-Fernández, S.; Benyei, P.; Calvet-Mir, L.; Junqueira, A. B.; Labeyrie, V.; LI, X.; Miñarro, S.; Porcher, V.; Porcuna-Ferrer, A.; Schlingmann, A.; et al. (Springer, 2024)
The effects of climate change depend on specific local circumstances, posing a challenge for worldwide research to comprehensively encompass the diverse impacts on various local social-ecological systems. Here we use a place-specific but cross-culturally comparable protocol to document climate change indicators and impacts as locally experienced and analyze their distribution. We collected first-hand data in 48 sites inhabited by Indigenous Peoples and local communities and covering all climate zones and nature-dependent livelihoods. We documented 1,661 site-agreed reports of change corresponding to 369 indicators. Reports of change vary according to climate zone and livelihood activity. We provide compelling evidence that climate change impacts on Indigenous Peoples and local communities are ongoing, tangible, widespread, and affect multiple elements of their social-ecological systems. Beyond potentially informing contextualized adaptation plans, our results show that local reports could help identify economic and non-economic loss and damage related to climate change impacts suffered by Indigenous Peoples and local communities.